Leadership lessons from compelling contexts - Peus, Claudia; Braun, Susanne, Dr.; Schyns, Birgit (Bingley, U.K. : Emerald, 2016)
This volume uses the idiosyncrasies of compelling contexts to teach fundamental leadership lessons that are applicable to other settings. Practitioners and researchers are challenged to deviate from standard models and provided with new ideas for leadership development.
Research into leadership often focuses on standard business organizations. We know little about these proposed models apply to leadership in other contexts, such as the military, sports, film and television industries or religious organizations. Here, we deliberately reverse the idea of investigating how standard models fit into non-standard contexts; we want to know what leadership lessons can be drawn from compelling yet understudied contexts. Research and theory from four types of contexts are presented: Those characterized by high levels of competition, such as sport, those in which the generation of innovation and creativity is crucial e.g. film and television, high-risk contexts such as the military and aviation, and those where fostering the well-being of others is at the core. To summarize, as much as we can learn about leadership from standard business organizations and apply it to unusual contexts, the same applies the other way round: Idiosyncrasies of compelling contexts teach us fundamental lessons about leadership which are also applicable to other settings.
Introduction: exploring compelling contexts through paradox, tension, and new approaches to leadership / Michelle Blight -- Leadership in the National Football League: do leaders make a difference? / Robert Lord, Suzanne Devlin, Carol Caldwell, Darrin Kass -- Following the leader in sports: a targeted review and a rally for extended research / Marco DiRenzo, Steven Weingarden, Christian Resick -- What lessons can we learn from football about leadership and management? / Birgit Schyns, Sarah Gilmore, Graham Dietz -- The role of leaders in managing envy and its consequences for competition in organizations / Theresa Floyd, Charles Hoogland, Richard Smith -- Paradox and challenges in military leadership / Ronit Kark, Tair Karazi-Presler, Sarit Tubi -- Leading high-risk teams in aviation / Gudela Grote -- Terrorist leaders - how ethical must they be? / Dina Al Raffie, Matthias Huehn -- Leadership lessons from creative industries: the case of producers, directors, and executives in film and television / Susan Murphy -- The "genre bender": the creative leadership of Kathryn Bigelow / Olga Epitropaki, Charalampos Mainemelis -- Children's stories as a foundation for leadership schemas: more than meets the eye / Peter Harms, Seth Spain -- Expertise coordination over distance: shared leadership in dispersed new product development teams / Miriam Muethel, Martin Hoegl -- Leadership in academia: individual and collective approaches to the quest for creativity and innovation / Susanne Braun, Claudia Peus, Dieter Frey, Kristin Knipfer -- Emotional labor among West Texas Baptist pastors: potential threats to leader authenticity and lessons learned / Kelly McCauley, William Gardner -- Finding meaning in highly uncertain situations: servant leadership during change / Dirk van Dierendonck, Milton Sousa -- Leadership in volunteer multistakeholder groups tackling complex problems / Kate Hilton, Ruth Wageman -- Conclusion: leadership lessons from compelling contexts / Claudia Peus, Susanne Braun, Birgit Schyns.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- General; Business & Economics -- Development -- Business Development; Business & Economics -- Management; Management and management techniques; Organizational theory and behaviour; Leadership; Management